Determination of Neurotransmitter in Biological and Drug Samples Using Gold Nanorods Decorated f-MWCNTs Modified Electrode. Issue 9 (22nd June 2018) - Govindasamy, Mani; Manavalan, Shaktivel; Chen, Shen-Ming; Rajaji, Umamaheswari; Chen, Tse-Wei; Al-Hemaid, Fahad M. A.; Ali, M. Ajmal; Elshikh, Mohamed Soliman
Abstract : We described a nanocomposite material that consists of gold nanorods self-assembled on functionalized multiwalled-carbon nanotubes (Au NRs@ f -MWCNTs). It was deposited on a screen-printed carbon electrode (SPCE) which then is well suited for sensitive and selective determination of dopamine. Au NRs are prepared by silver ion-assisted seed-mediated method and the Au NRs@f-MWCNTs was prepared by self-assembly of Au NRs on f -MWCNTs. The composite was characterized by X-ray diffraction, transmission electron microscopy, Raman, UV-visible, and energy-dispersive X-ray spectroscopy. The electrochemical analyses were carried out using inexpensive SPCE to modify nanocomposite and visualized signals by cyclic voltammetry and amperometric instrument. The electrode displays excellent electrocatalytic ability to catalyze the redox reaction of dopamine. The modified SPCE, best operated at a working potential as low as 0.12 V (vs. Ag/AgCl), responds linearly to dopamine in the 3.5 nM to 1550 μM concentration range. The detection limit is 5.0 × 10 −10 (±0.82) M, and the sensitivity is 4.04 (±0.58) μA.μM −1 .cm −2 . The limit of quantification (LOQ) of the method was 16.6 × 10 −10 (±1.2) M. The sensor has good selectivity, appreciable stability, and reproducibility. It was applied to the determination of dopamine in (spiked) human serum and rat brain samples.